SOFTWARE REUSE PRACTICES AND SOFTWARE DEVELOPMENT EFFICIENCY. A PLS-SEM APPROACH - Laviza Asif Memon; Humair Khan Bughio; Anjum Ara; Zeeshan Qureshi (Spectrum of Engineering Sciences, 2025)
In the current competitive environment of software business, the efficiency in development is important in speeding up delivery of high-quality products. This paper examines the effectiveness that three important software reuse practices, the use of design patterns, reusable components, and adoption of frameworks have on efficiency in software development in terms of time to market, density of bugs and productivity by developers. A structured survey was used to collect the data by conducting it on 117 software professionals of Karachi, Pakistan. The conceptual model was enabled by the study using Partial Least Squares Structural Equation Modeling (PLS-SEM) in which all the hypothesized relationships were proved statistically significant. The outcomes reveal that reuse of software practice highly decreases the time to market and the density of bugs and increases the productivity of the developer. Framework acquisition was the single factor to influence the time to market the most, and reusable components influenced productivity the most. Such results provide empirical evidence to the value of adopting reuse strategies during development processes and will also become part of knowledge content in the field of software engineering because they also qualify the effectiveness of architectural reuse. The paper also has practical implications to technology managers seeking to increase their development performance using the structured reuse practices.